2012
DOI: 10.1186/1471-2458-12-257
|View full text |Cite
|
Sign up to set email alerts
|

Association between binge drinking, type of friends and gender: A cross-sectional study among Brazilian adolescents

Abstract: BackgroundHazardous drinking among adolescents is a major public health concern. The purpose of this study was to examine the prevalence of binge drinking/alcohol consumption and its association with different types of friendship networks, gender and socioeconomic status among students in Belo Horizonte, Minas Gerais, Brazil.MethodsWe conducted a cross-sectional study on a representative random sample of 891 adolescents (41% male, aged 15–19 years) from public and private schools in 2009–2010. Information on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 59 publications
9
44
2
1
Order By: Relevance
“…In Brazil, Sanchez et al 7 found a binge drinking rate of 32% among students in all five Brazilian macro regions. A similar prevalence rate was found among students aged 15 to 19 years in the city of Belo Horizonte (36%) 8 .…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…In Brazil, Sanchez et al 7 found a binge drinking rate of 32% among students in all five Brazilian macro regions. A similar prevalence rate was found among students aged 15 to 19 years in the city of Belo Horizonte (36%) 8 .…”
Section: Introductionsupporting
confidence: 76%
“…Binge drinking is often associated with the use of other substances, such as cigarettes 37 . This association may be explained by common predisposing factors, such as the influence of peers, parental behavior regarding alcohol, tobacco and supervision 1 as well as aspects related to religious participation 8,38 . In contrast to the present findings, Fisher et al 39 conducted a cohort study in the United States and concluded that smoking did not appear to increase the risk of binge drinking among individuals who had initiated alcohol use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A par das atitudes e comportamentos dos pais e familiares face ao consumo, as atitudes e comportamentos dos grupos de pares face a bebidas alcoólicas são os fatores de risco mais frequentemente referidos na literatura como fortemente associados ao consumo de álcool (Zarzar, et al, 2012;Svensson, 2010;Bekman, Cummings & Brown, 2010). A disponibilidade financeira, ou o dinheiro disponível para despesas pessoais, embora menos referida pela literatura, surge igualmente como fator de risco para o consumo (Donath et al, 2012).Embora no presente estudo o prazer decorrente do consumo de bebidas alcoólicas tenha sido identificado por todos os grupos enquanto fator de risco para o consumo regular, o mesmo raramente é referido pela literatura.…”
Section: Discussionunclassified
“…When examining binge drinking among Brazilian adolescents, Zarzar et al [12] concluded that gender, friendship networks, and social vulnerability are strongly correlated with excessive alcohol consumption. Finally, personality traits also play an important role in alcohol use.…”
Section: Introductionmentioning
confidence: 99%